Criticism of the Representation of Islam in Western Media and the Role of Da'wah in Transformation - Karimullah, Suud Sarim (STAI Bumi Silampari, 2023)
The study reveals an in-depth analysis of the representation of Islam in the Western media, highlighting the issues of bias and stereotypes that still often color Western views of Islam and the Muslim community. This study uses a literature study with integrative literature analysis to obtain comprehensive results. The results of the study stated that the representation of Islam in the Western media has a significant role in shaping the views and understanding of Western society about Islam. These representations are not always objective and are often influenced by biases and stereotypes that develop, which later become the object of sharp criticism. Criticism of the representation of Islam in Western media raises issues of injustice, imbalance, and potential for Intercultural conflict. However, in this context, the role of da'wah, which focuses on delivering accurate messages, peace values, and rejection of extremism, has positively contributed to changing media representation. Whether conducted through traditional media or online platforms, da'wah can shape a more balanced narrative, overcome biases, and educate the Western public about Islam. Therefore, efforts to continue promoting an educative and peace-oriented da'wah are important in shaping a better and objective representation of Islam in Western media.